KARSTIFICATION AND ITS INFLUENCE ON GROUNDWATER FLOW AND PERMEABILITY IN CARBONATE AQUIFERS: A LITERATURE REVIEW - Isman Saleh (PT. Jurnal Center Indonesia Publisher, 2026)
Karstification is the dominant geological process controlling groundwater circulation and permeability in carbonate aquifers. Through the dissolution of carbonate rocks, karst processes create highly heterogeneous systems characterized by fractures, conduits, and interconnected channel networks that significantly influence groundwater flow dynamics. This literature review aims to synthesize current knowledge regarding the effects of karst on water circulation and permeability in carbonate aquifers based on hydrogeological, hydrochemical, geophysical, and numerical modeling studies from various regions worldwide. The review shows that karstification substantially enhances hydraulic conductivity and produces complex flow regimes ranging from diffuse fracture flow to turbulent conduit flow. The epikarst zone plays an important role in regulating infiltration and recharge distribution, while tectonic structures such as faults and fractures strongly control groundwater pathways and aquifer compartmentalization. Karst aquifers also exhibit strong spatial variability in permeability, making groundwater flow and contaminant transport difficult to predict using conventional hydrogeological approaches. In addition, the integration of equivalent porous medium (EPM), discrete fracture network (DFN), and conduit network (CN) models is essential for accurately representing karst aquifer behavior. Understanding the influence of karstification on groundwater circulation is therefore crucial for sustainable groundwater management and aquifer vulnerability assessment, particularly in regions facing increasing water demand and climate change pressures.